2021
DOI: 10.3390/ijms22052381
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the Inflammatory Responses in Fabry Patient iPSC-Derived Cardiovascular Endothelial Cells by CRISPR/Cas9-Corrected Mutation

Abstract: The late-onset type of Fabry disease (FD) with GLA IVS4 + 919G > A mutation has been shown to lead to cardiovascular dysfunctions. In order to eliminate variations in other aspects of the genetic background, we established the isogenic control of induced pluripotent stem cells (iPSCs) for the identification of the pathogenetic factors for FD phenotypes through CRISPR/Cas9 genomic editing. We adopted droplet digital PCR (ddPCR) to efficiently capture mutational events, thus enabling isolation of the correcte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Recently, Song and co-workers reported that pro-inflammation pathway are activated within the cells with Fabry pathology. While the inflammatory responses can be reversed using gene therapy, further confirming the correlation between inflammatory activation and Fabry pathology (Song et al, 2021). Several molecular pathways have been reported to be attributed to the inflammatory activation of Fabry disease, including the nuclear factor kappa B (NF-κB) pathway, oxidative stress, and transforming growth factor-β (TGF-β) pathway.…”
Section: Controlling Inflammatory Responses Can Help Restoring Host H...mentioning
confidence: 79%
“…Recently, Song and co-workers reported that pro-inflammation pathway are activated within the cells with Fabry pathology. While the inflammatory responses can be reversed using gene therapy, further confirming the correlation between inflammatory activation and Fabry pathology (Song et al, 2021). Several molecular pathways have been reported to be attributed to the inflammatory activation of Fabry disease, including the nuclear factor kappa B (NF-κB) pathway, oxidative stress, and transforming growth factor-β (TGF-β) pathway.…”
Section: Controlling Inflammatory Responses Can Help Restoring Host H...mentioning
confidence: 79%
“…In addition, the mechanism of endothelial cell damage by lyso‐Gb3 includes cytokines, abnormalities in the immune system, and vascular damage caused by increased reactive oxygen species 19–21 . Furthermore, increases in inflammatory cytokines and ROS were observed in vascular endothelial cells differentiated from iPSCs derived from patients with FD 25,33 …”
Section: Discussionmentioning
confidence: 99%
“…This leads to an accumulation of globotriaosyceramide (GB3) in ECs of many tissues that can result in multiple organ failure, and dysfunction of endothelial cells in the microvasculature. Using this isogenic iPSC control line to derive ECs, they demonstrated a reversal of inflammatory responses, including decreased cytokine release and specific inflammatory markers such as ICAM, CCL2CCL5, CXCL1, IL6, IL8, monocyte inducible factor, and CXCL10 [ 35 ]. The importance of using isogenic controls is highlighted in this monogenetic rare vascular disease model, allowing the examination of pathologic phenotypes in a system without the modeling limitations of using healthy control lines, such as epigenetic, environmental, and genetic background differences.…”
Section: Vascular Disease Modelsmentioning
confidence: 99%